GOOD CORPORATE GOVERNANCE DALAM MENINGKATKAN KEPUASAN MUZAKKI DI BADAN AMIL ZAKAT NASIONAL - Hana Septi Kuncaraningsih; Muhammad Rasyid Ridla (Jurnal MD, 2015)
This research is aimed to find empirical evidence the influence of GoodCorporate Governance toward muzakki satisfaction on badan amil zakatnasional (BAZNAS) in Sleman-Yogyakarta. Good corporate governance isa concept that important to stakeholder, forming to make institutions freecorruption, transparent, and professional. The research is uses quantitaveapproach. The data analysis using three tests of hypothesis, including rankspearman correlation coefficient, coefficient determination and simple linearregression. All hypothesis testing of the statement result in significant value.It can be concluded influence of Good Corporate Governance in positive andsignificant toward muzakki satisfaction, by the amount contributions of16,3%. The research is expected to provide a new idea for a public institutionto apply the concept of good corporate governance.Keywords: Good Corporate Governance, Muzakki Satisfaction, BAZNASSleman